PREDIKSI KELULUSAN MAHASISWA TEPAT WAKTU MENGGUNAKAN METODE DESICION TREE DAN ARTIFICIAL NEURAL NETWORK - Rohmawan, Eko Prasetiyo (JURNAL ILMIAH MATRIK, 2018)
Students graduation on time is one of assessment in accreditation process of university. The problem is how to know the students will be able to pass on time or not. In this study focus on how the prediction of graduation students on time with data mining using decision tree algorithm and artificial neural network. This research uses data of students who have passed the data as training and students who have not passed as data testing. This study aims to determine the graduation of students on time or not, the expected results can provide information and input for universities in making policy for improvement in the future. Keywords: Graduation, Data Mining, Decision Tree, Artificial Neural Network